2006
DOI: 10.1210/jc.2005-2839
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxicosis after Denileukin Diftitox Therapy in Patients with Mycosis Fungoides

Abstract: Monitoring thyroid function before and during treatment with denileukin diftitox is recommended. Symptomatic thyrotoxicosis may be missed due to other acute reactions to the drug, and subsequent hypothyroidism may develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It is approved for use in cutaneous T-cell lymphoma and graft-versus-host disease after allogenic stem cell transplant (86,87). In a retrospective study, eight patients showed TPO-Ab and thyrotoxicosis within 1-35 days of treatment; five of them eventually developed permanent hypothyroidism (88). Autoimmunity could not be the mechanism of DD-induced thyroid toxicity, because the IL2-component of the drug does not activate the IL2-lymphocyte receptor.…”
Section: Denileukin Diftitoxmentioning
confidence: 99%
See 1 more Smart Citation
“…It is approved for use in cutaneous T-cell lymphoma and graft-versus-host disease after allogenic stem cell transplant (86,87). In a retrospective study, eight patients showed TPO-Ab and thyrotoxicosis within 1-35 days of treatment; five of them eventually developed permanent hypothyroidism (88). Autoimmunity could not be the mechanism of DD-induced thyroid toxicity, because the IL2-component of the drug does not activate the IL2-lymphocyte receptor.…”
Section: Denileukin Diftitoxmentioning
confidence: 99%
“…Autoimmunity could not be the mechanism of DD-induced thyroid toxicity, because the IL2-component of the drug does not activate the IL2-lymphocyte receptor. The absence of IL2-receptors on thyrocytes excludes direct thyroid toxicity (88). However, DD might target and lyse intrathyroidal lymphocytes with local release of cytokines leading to thyroiditis/ thyrotoxicosis (88).…”
Section: Denileukin Diftitoxmentioning
confidence: 99%
“…Of note, Dd should not be administered in a facility ill equipped to provide cardiopulmonary resuscitation. Severe and persistent transaminitis, thyrotoxicosis, loss of visual acuity or color vision, and rhabdomyolysis have been reported but are uncommon [240,[246][247][248]. Investigations combining Dd with conventional chemotherapeutic agents are ongoing.…”
Section: Denileukin Diftitoxmentioning
confidence: 99%
“…Thyrotoxicosis has been identified in patients treated with interferon-a interleukin, lithium, denileukin diftitox, and leuprolide acetate (108,109,(165)(166)(167)(168)(169). Usually these medications cannot be stopped; therefore, the key is to determine whether the thyroid has high or low uptake of 123 I.…”
Section: Thyrotoxicosis Attributable To Nonthyroid Medicationsmentioning
confidence: 99%
“…The key is to obtain an uptake measurement, and when the value is low the course is similar to that of silent thyroiditis (165,176). Eight patients with mycosis fungoides became thyrotoxic during treatment with denileukin diftitox (167). Denileukin diftitox is a recombinant fusion protein consisting of the ligand binding region of interleukin 2 and diphtheria toxin.…”
Section: Thyrotoxicosis Attributable To Nonthyroid Medicationsmentioning
confidence: 99%